1999
DOI: 10.1021/ie980722n
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Absorption of CO2 in Alkaline Buffer Solutions:  Joint Action of Two Enhancers

Abstract: We measured the absorption of CO2 in alkaline 0.5 M/0.5 M sodium carbonate/bicarbonate buffers containing either saccharose and sodium arsenite or saccharose and formaldehyde. Absorption enhancement increased upon increasing the concentration of either of the catalysts, but the joint action of the two was always less than the sum of their individual effects, the difference being a function of the acidities and concentrations of the catalysts and the pH of the carbonate/bicarbonate buffer solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Hence most of these catalysts have been evaluated for their activities at pH > 10. The molecules tested were acetaldehyde hydrate, acetate, arginine, arsenite, , arsenious acid, boric acid, ,, butyl chloral hydrate, chloral hydrate, chloral alcoholate, diacetyl hydrate, hypobromous acid, hypochlorous acid, , copper sulfate, ethanol, formaldehyde, ,, fructose, germanic acid, , glucose, glycerin, glycine, glyoxal hydrate, methanol, phosphate, , phosphite, proline, rhodium hydride, methylene glycol, saccharose, sarcosine, selenic acid, , silicic acid, , vanadium­(V) oxide, telluric acid, , sodium acetate, sodium bisulfate, sodium orthovanadate and zinc sulfate . Most of these inorganic chemicals have different oxidation states depending on pH .…”
Section: Catalyzed Hydration Of Co2mentioning
confidence: 99%
“…Hence most of these catalysts have been evaluated for their activities at pH > 10. The molecules tested were acetaldehyde hydrate, acetate, arginine, arsenite, , arsenious acid, boric acid, ,, butyl chloral hydrate, chloral hydrate, chloral alcoholate, diacetyl hydrate, hypobromous acid, hypochlorous acid, , copper sulfate, ethanol, formaldehyde, ,, fructose, germanic acid, , glucose, glycerin, glycine, glyoxal hydrate, methanol, phosphate, , phosphite, proline, rhodium hydride, methylene glycol, saccharose, sarcosine, selenic acid, , silicic acid, , vanadium­(V) oxide, telluric acid, , sodium acetate, sodium bisulfate, sodium orthovanadate and zinc sulfate . Most of these inorganic chemicals have different oxidation states depending on pH .…”
Section: Catalyzed Hydration Of Co2mentioning
confidence: 99%
“…Vazquez et al (7,10) observed that certain solute such as glycerin and commercial sugar had increased the absorption rate of carbon dioxide in a wetted wall column .This increase in the absorption rate is related to the structural similarities and the inorganic and enzymatic solutes . (8,9) Vazque G. etal (10) studied absorption of carbon dioxide in alkaline .5M sodium carbonate/.5M bicarbonate buffers containing two enhancers. The used enhancers are either saccharose and sodium arsenite or saccharose and formaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, aqueous solutions of amines are used to enhance the absorption rate of the process with respect to the physical absorption. These processes are carried out in aqueous single-solute or binary-solute solutions that produce an increase of the absorption enhancement factor. , The use of blended amines 3,4 or the sterically hindered amines 5,6 leads to a considerable improvement in absorption and a great savings in energy.The simultaneous presence of fine activated carbon particles and one or several amines in aqueous suspensions constitutes a system of considerable interest. …”
Section: Introductionmentioning
confidence: 99%